Multivariate genome-wide association study of rapid automatised naming and rapid alternating stimulus in Hispanic American and African–American youth. Issue 8 (17th April 2019) - Truong, Dongnhu Thuy; Adams, Andrew Kenneth; Paniagua, Steven; Frijters, Jan C; Boada, Richard; Hill, Dina E; Lovett, Maureen W; Mahone, E Mark; Willcutt, Erik G; Wolf, Maryanne; Defries, John C; Gialluisi, Alessandro; et al.
Abstract : Background: Rapid automatised naming (RAN) and rapid alternating stimulus (RAS) are reliable predictors of reading disability. The underlying biology of reading disability is poorly understood. However, the high correlation among RAN, RAS and reading could be attributable to shared genetic factors that contribute to common biological mechanisms. Objective: To identify shared genetic factors that contribute to RAN and RAS performance using a multivariate approach. Methods: We conducted a multivariate genome-wide association analysis of RAN Objects, RAN Letters and RAS Letters/Numbers in a sample of 1331 Hispanic American and African–American youth. Follow-up neuroimaging genetic analysis of cortical regions associated with reading ability in an independent sample and epigenetic examination of extant data predicting tissue-specific functionality in the brain were also conducted. Results: Genome-wide significant effects were observed at rs1555839 (p=4.03×10 −8 ) and replicated in an independent sample of 318 children of European ancestry. Epigenetic analysis and chromatin state models of the implicated 70 kb region of 10q23.31 support active transcription of the gene RNLS in the brain, which encodes a catecholamine metabolising protein. Chromatin contact maps of adult hippocampal tissue indicate a potential enhancer–promoter interaction regulating RNLS expression. Neuroimaging genetic analysis in an independent, multiethnic sample (n=690) showed that rs1555839 is associated with structural variation in the right inferior parietal lobule. Conclusion: This study provides support for a novel trait locus at chromosome 10q23.31 and proposes a potential gene–brain–behaviour relationship for targeted future functional analysis to understand underlying biological mechanisms for reading disability.